Perceived corporate social responsibility and pro-environmental behaviour: Insights from business schools of Peshawar, Pakistan - Tariq, Sana; Yunis, Mohammad Sohail; Shoaib, Shandana; Abdullah, Fahad; Khan, Shah Wali (Frontiers in Psychology, 2022)
Corporate Social Responsibility and environmental sustainability has become a pressing issue of modern organizations. Attending to the call of scholars concerning micro foundations of corporate social responsibility, this study focuses on the interplay between corporate social responsibility perceptions and pro-environmental behavior. It also unveils the underlying mechanism that how perceived CSR shapes pro-environmental behaviour in an under-studied developing context. Empirically, a qualitative multiple-case study design is adopted by selecting three business schools of Peshawar, Pakistan. Data are collected through fourteen semi-structured interviews conducted with top management and faculty members. A qualitative documentary review is also used to supplement primary data. Thematic network technique is used for data analysis. Plantation, cleanliness, waste reduction and energy conservation constitute the environmental dimension of employees’ perceived CSR. Moreover, perceived CSR shapes pro-environmental behavior through environmental knowledge and awareness, eco-civics sense, environmental values, personality traits, religious perspective and perceived organizational support for environment. This enquiry makes novel contribution in CSR literature by proposing eco-civic sense and religious perspective as new CSR drivers concerning pro-environmental behavior. Embracing stakeholder salience in the context of current study also takes CSR research a step further. Findings are also useful for the management in order to make CSR agenda of business schools more strategic, broad and focused on salient stakeholders’ priorities.